Phenol content in the marine environments of the coastal waters in Peter the Great Bay, Japan Sea - O. V. Badmaev (Известия ТИНРО, 2024)
Total content of phenols in seawater and bottom sediments of some water areas in Peter the Great Bay in 1998–2022 is considered. Mean annual values of phenol concentration exceeded the maximum allowable level for the water of fishing grounds but were comparable with the background concentrations in water and bottom sediments. Peaks of phenol concentration were usually observed in the estuaries of rivers, so the rivers are considered as the main source of phenol pollution: the Razdolnaya in the Amur Bay, the Shkotovka and Artemovka in the Ussuri Bay, and the Obyasnenie in the Zolotoy Rog Bay. Other significant sources of pollution were the urban wastewater discharged to the eastern Amur Bay and wastes of shipbuilding and ship repair plants and marine vessels. Downward trend of the total phenol content was revealed for all water areas, but pollution of bottom sediments by phenols was still high in the Ussuri Bay in 2019–2022.